Penerapan Augmented Reality Pada Media Pembelajaran Sains di Sekolah Dasar Swasta - Andriyanto, Sidhiq; Parulian Silalahi; Fateh Tikal Zamzami (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research focuses on developing an interactive augmented reality learning media to address the problem of low learning interest and understanding of science concepts at SDS Maria Goretti Sungailiat, particularly on the topics of photosynthesis, energy transformation, states of matter, and force effects. The augmented reality application was developed through six stages of MDLC - concept, design, material collecting, assembly, testing, and distribution - using Unity 3D and Vuforia as the AR development platform, Canva for graphic design, and Autodesk Maya for 3D object modeling. After undergoing functionality and compatibility testing, the application was confirmed to work properly. Subsequent User Acceptance Testing (UAT) with 34 fourth-grade students at SDS Maria Goretti showed that this media successfully improved students' understanding by 87.4%, proving that the use of AR can be an effective solution for visualizing abstract science concepts to make them easier to comprehend.